2022
DOI: 10.3390/ijms23116182
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Efficiency through dsRNA Injection Is Enhanced by Knockdown of dsRNA Nucleases in the Fall Webworm, Hyphantria cunea (Lepidoptera: Arctiidae)

Abstract: RNA interference (RNAi) technology is a promising approach used in pest control. The efficiency of RNAi varies considerably among different insect species, and growing evidence suggests that degradation of double-stranded RNA (dsRNA) prior to uptake is an important factor that limits RNAi efficiency in insects. Our recent work on fall webworm (Hyphantria cunea), an important invasive pest in China, showed a relatively low silencing efficiency of RNAi through dsRNA injection, which is considered the most feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…Recent studies have found 4 dsRNases in H. cunea , HcdsRNase1 , HcdsRNase2 , HcdsRNase3 , and HcdsRNase4 (Zhang et al. , 2022). There are 3 different dsRNases in Cylas puncticollis and 5 dsRNases in the tobacco cutworm Spodoptera litura (Peng et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found 4 dsRNases in H. cunea , HcdsRNase1 , HcdsRNase2 , HcdsRNase3 , and HcdsRNase4 (Zhang et al. , 2022). There are 3 different dsRNases in Cylas puncticollis and 5 dsRNases in the tobacco cutworm Spodoptera litura (Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SgdsRNase1, SgdsRNase3, and SgdsRNase4, which are also highly expressed in the midgut, do not affect RNAi efficiency (Wynant et al, 2014). Recent studies have found 4 dsRNases in H. cunea, HcdsRNase1, HcdsRNase2, HcdsRNase3, and HcdsRNase4 (Zhang et al, 2022). There are 3 different dsRNases in Cylas puncticollis and 5 dsRNases in the tobacco cutworm Spodoptera litura (Peng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Among these factors, the stability of dsRNA in vivo is considered to be the critical element for the variable RNAi efficiency in insects. 17,[32][33][34] Many recent studies have focused on the factors affecting dsRNA stability in living insects, mainly referring to the dsRNA degradation attributed to the exocellular nuclease in the gut, 26,27,35 hemolymph, 28,30,36,37 and salivary secretions. 38,39 However, little attention has been paid to the stability of dsRNA in vitro prior to being administered into insects.…”
Section: Introductionmentioning
confidence: 99%
“…Em Hyphantria cunea (Lepidoptera), usando o gene chitinase 5 (Cht5) como genealvo, demonstrou-se que silenciar genes que codificam dsRNases (especialmente HcdsRNase3 e HcdsRNase4) aumenta significativamente a eficácia de RNAi via injeção de dsHcCht5, e co-silenciar esses dois genes HcdsRNases resultam em uma melhora ainda mais significativa na eficácia (Zhang et al, 2022). Também, em Cnaphalocrocis medinalis (Lepidoptera), o cosilenciamento de CmCHS (quitina sintase de C. medinalis) e CmdsRNase afetou significativamente o crescimento e desenvolvimento do inseto e, assim, melhorou a eficácia do RNAi .…”
Section: Identificação Do Geneunclassified